2013
DOI: 10.1055/s-0033-1349089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beta-Cyclodextrin on Percutaneous Absorption of Commonly Used Eusolex® Sunscreens

Abstract: Considering the ability of β-CDX complexation in the reduction of flux and enhancement ratio as well as prolongation of absorption lag time, this technique could be very helpful for reducing systemic absorption of the UV filters and subsequent toxicity and allergic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Shokri et al [36] investigated the fate of AVO, BP-3 and ESZ formulated in a cosmetic O/W emulsion as free filters or included in a complex with β-cyclodextrin in permeation studies through abdominal skin of Wistar rats, which were shaved with razors 24 h prior of the experiments. It is necessary to emphasize that these products are among the most common UV filters on the market and that, after cutaneous application, in vivo have been demonstrated to permeate the skin in significant amounts.…”
Section: In Vitro Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shokri et al [36] investigated the fate of AVO, BP-3 and ESZ formulated in a cosmetic O/W emulsion as free filters or included in a complex with β-cyclodextrin in permeation studies through abdominal skin of Wistar rats, which were shaved with razors 24 h prior of the experiments. It is necessary to emphasize that these products are among the most common UV filters on the market and that, after cutaneous application, in vivo have been demonstrated to permeate the skin in significant amounts.…”
Section: In Vitro Methodsmentioning
confidence: 99%
“…In order to increase the dimension of the solar filter and its concentration in the upper stratum corneum, the formation of inclusion complexes with cyclodextrins has been investigated, also to increase the sunscreen photostability. Shokri et al [36] prepared an inclusion complex of β-cyclodextrin with three different UV filters (AVO, BP-3 and ESZ) by different methods, i.e., co-evaporation, grinding and kneading. They found that the complexation reduced the rate of permeation of sunscreens with respect to when the free filter was taken in account, also increasing the lag time, while the physical mixture affected permeation only for a little extent.…”
Section: Formulation Strategiesmentioning
confidence: 99%
“…Al-Rawashdeh et al (2010) reported the micro-encapsulation of commercial UV filters (oxybenzone ( 10 ), EHMC ( 21 ), and octocrylene ( 30 )) in hydroxypropyl-β-cyclodextrins system that successfully acted as photostabilisers [ 44 ]. Studies with cyclodextrins encapsulation using other UV filters have been also reported [ 45 , 46 , 47 ]. Moreover, the stabilisation of avobenzone ( 11 ) mediated by the combination with other UV filters, such methylbenzylidene camphor ( 7 ) or octocrylene ( 30 ) [ 48 ], or with bis-ethylhexyloxyphenol methoxyphenyl triazine ( 27 ) [ 35 ], was proved as an advantageous option that confers more stability to the photounstable UV filters.…”
Section: Challengesmentioning
confidence: 99%
“…Likewise, the inclusion complex of oxybenzone in HPβ-CD and sulfobutylether-β-CD (SBE-β-CD) led to an increase in the aqueous solubility of oxybenzone (up to 1049-fold) whilst significantly limiting its percutaneous absorption (Figure 7) [81]. Furthermore, Shokri et al reported that the absorption lag time and overall percutaneous flux of avobenzone, oxybenzone, and ensulizole were reduced by 4 to 15-fold after complexation with β-CD [82]. Due to its relatively low price and its absorption of both UVA and UVB radiation, UV filter benzophenone-3 is regularly used in sunscreen formulations.…”
Section: Uv Filters/cds Inclusion Complexmentioning
confidence: 99%